2011
DOI: 10.1248/bpb.34.624
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Genetic Contents Variations in Clinical Candida albicans Isolates

Abstract: Candida albicans is the most common fungal pathogen, causing skin and mucosal infections in generally healthy individuals, life-threatening infections in immunocompromised patients, and leading to death in up to 50% of patients with bloodstream infections. 1,2)C. albicans is known for its unstable genome. The instability of the chromosome copy number of entire chromosomes, as well as the large portions of chromosomes was extensively studied with laboratory and freshly isolated strains using pulse-field gene el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…This is consistent with earlier studies that revealed karyotypic variation in multiple C. albicans isolates (Suzuki et al 1982;Rustchenko-Bulgac 1991;Perepnikhatka et al 1999;Selmecki et al 2006;Rustchenko 2007;Bouchonville et al 2009;Yang et al 2011). In the current study, seven of the 21 strains contained trisomic chromosomes, with Chr 4 and Chr 7 being trisomic in multiple isolates.…”
Section: Aneuploidy In C Albicanssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with earlier studies that revealed karyotypic variation in multiple C. albicans isolates (Suzuki et al 1982;Rustchenko-Bulgac 1991;Perepnikhatka et al 1999;Selmecki et al 2006;Rustchenko 2007;Bouchonville et al 2009;Yang et al 2011). In the current study, seven of the 21 strains contained trisomic chromosomes, with Chr 4 and Chr 7 being trisomic in multiple isolates.…”
Section: Aneuploidy In C Albicanssupporting
confidence: 93%
“…Analysis of the 21 C. albicans genomes revealed gene copy number variation, including transposons that have previously been shown to be active and to have differential representation between strains Holton et al 2001;Yang et al 2011). Variable copy number was also observed for the CYP5 gene that encodes a cytoplasmic cyclophilin.…”
Section: Copy Number Variation and Positive Selectionmentioning
confidence: 92%
“…We previously revealed that the copy numbers of ORF19.7274 and ORF19.7275 of the Zorro2 retrotransposon were increased in several clinical isolates compared with SC5314 by array-based comparative genomic hybridization analysis. 21) In this study, the transcription of Zorro2 was found up-regulated in strains in response to shorttime MCZ stress. Additional copies of Zorro2 were observed in the genome of derivative strains under long-term treatment of MCZ, suggesting that the Zorro2 has been transposed in the derivative strains with resistance to azole drugs.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have reported that retrotransposons, including Tca2, Tca5, Zorro1 and Zorro3, can be activated by temperature changes in C. albicans, [15][16][17]20) but no evidence has yet been provided to prove the transcription or transposition activity for Zorro2 in C. albicans. In this study, we showed that the Zorro2 retrotransposon in C. albicans was transcriptionally activated and transposed in response to MCZ, probably caused by the induction of endogenous ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of DNA copies from five Candida species was performed by qPCR with previously described primers , derived from the ITS2 regions of C. albicans, C. glabrata , C. parapsilosis , C. dubliniensis and C. tropicalis . Reactions were carried out with SYBR Green Master Mix (Applied Biosystems, Foster City, CA, USA), in a StepOne™ Real‐Time PCR System (Applied Biosystems) with one cycle of 10 min at 95°C; 40 cycles of 15 s at 95°C, 1 min at 60°C; and a final extension cycle at 72°C for 15 s.…”
Section: Methodsmentioning
confidence: 99%